Perceived professional preparedness of senior nursing students' questionnaire: Development and psychometric evaluation. (October 2020) - Shahsavari, Hooman; Bakhshi, Fatemeh; Khosravi, Afifeh; Najafi, Zahra; Ghorbani, Azam
Abstract: Background: Nursing students' perceptions of their professional preparedness help them perform their independent nursing role with self-confidence. Objectives: To develop and psychometric testing of an instrument, the "Perceived Professional Preparedness of senior Nursing Students" questionnaire. Design: Mixed-method exploratory study. Methods: We conducted this study in two phases: (1) development of initial questionnaire through interview and literature review; (2) evaluation of psychometric properties of the instrument to introduce a reliable, valid tool. Settings and participants: We assessed qualitative and quantitative face validity of initial questionnaire by administering it to 10 nursing students. Then, a panel of 10 nursing specialists determined the Content Validity Index. After modifying items, we assessed the construct validity of the 45-item questionnaire. A sample of 159 senior nursing students completed the questionnaire, and we conducted exploratory and confirmatory factor analysis using this data. To assess the test-retest reliability, 30 students completed the instrument twice with a two-week time interval. Results: The Content Validity Index with the modified Kappa coefficient was calculated as ≥0.72, which is considered satisfactory. In exploratory factor analysis using the maximum likelihood method and varimax rotation, we extracted 19 items in four factors. This structure included 61.91% of the total variance. The factors were clinical competency, evidence-based practice, framework-oriented performance, and patient-centered care. Cronbach's alpha coefficient and McDonald's omega values higher than 0.70 and inter-class correlation coefficient above 0.90 for all factors confirmed reliability. Confirmatory factor analysis indicated a suitable fitting of the final developed model. Conclusion: The developed questionnaire is a valid, reliable tool to assess the perceived preparedness of senior nursing students for transition to the clinical setting. Further psychometric testing for this questionnaire on larger populations and in different contexts is suggested.